The Toxicity of Environmental Pollutants - Junqueira Dorta, Daniel; Palma de Oliveira, Danielle (IntechOpen, 2022)
Given the widespread presence of chemical compounds in the environment and their effects on organisms, there is an increasing need to better understand the mechanisms underlying their toxicity. This book brings together 13 chapters on a variety of topics from different areas of research in environmental pollutants toxicology. While it illustrates the toxic effects of several environmental contaminants on humans and the biota, it also introduces methodologies for assessing environmental contamination as well as remediation techniques.